Developing Tobacco Control Interventions in Permanent Supportive Housing for Formerly Homeless Adults. Issue 6 (November 2020) - Alizaga, Natalie M.; Nguyen, Tram; Petersen, Anne Berit; Elser, Holly; Vijayaraghavan, Maya
Smoke-free policies are effective population-based strategies to reduce tobacco use yet are uncommon in permanent supportive housing (PSH) for formerly homeless individuals who have high rates of smoking. In this study, we partnered with six supportive housing agencies in the San Francisco Bay Area to examine the implementation of smoke-free policies and cessation services. We administered a questionnaire and conducted in-depth, semistructured interviews with agency directors (n = 6), property management staff (n = 23), and services staff (n = 24) from 23 PSH sites on the barriers to implementing tobacco control interventions. All properties restricted smoking in indoor shared areas, but only two had policies restricting smoking in living areas. While there was staff consensus that smoke-free policies were important to reduce tobacco-related harm, participants disagreed on whether smoke-free policies were aligned with PSH's harm reduction framework. Residents' comorbid mental illness and substance use and the lack of appropriate enforcement tools were barriers to implementation. Using these formative findings, we present a framework for a toolkit of strategies to increase implementation of smoke-free policies and cessation interventions in PSH. Successful implementation of indoor smoke-free policies in PSH will require concurrent cessation services to support smoking cessation efforts and address the mental health and substance use needs of residents.